Pengenalan Teknologi Network Cablink di Sekolah Menengah Kejuruan (SMK X) melalui Program Kreativitas Mahasiswa (PKM) untuk Siswa - Reko Syarif Hidayatullah; Halimatus Sadiah; Heri Setiawan; Irnawati Irnawati; Ana Rusdiana (Lembaga Pengembangan Kinerja Dosen, 2025)
The Student Creativity Program (PKM) aims to introduce Cablink network technology to students of Vocational High School (SMK) X as a form of strengthening competency in the field of Computer and Network Engineering. This activity includes the delivery of materials, installation, and hands-on practice in installing Cablink networks. The implementation method uses a participatory approach that allows students to be more active in understanding the material presented. With this approach, it is hoped that students can gain a deeper and more applicable understanding of developing network technology. During the activity, students are not only given theoretical explanations about Cablink networks, but also given the opportunity to be directly involved in the installation process, which provides very useful practical experience. The results of this activity show an increase in students' understanding of basic network concepts and technical skills in installing Cablink networks. This improvement is not only limited to the theoretical aspect, but also includes practical skills that can be directly applied in the world of work. This program is expected to be a bridge between the needs of the modern network industry and the readiness of SMK graduates to compete in the world of work. With the skills acquired through this activity, students are expected to be better prepared to face the challenges of rapidly developing technology in the fields of computers and networks. Furthermore, this activity also serves to introduce students to technologies relevant to industry needs, so they are better prepared to enter the professional world upon graduation. This program is expected to contribute to improving the quality of education at SMK X and provide significant benefits for developing students' skills in Computer and Network Engineering.